(untitled) (Bangladesh Critical Care Journal, 2017)
Introduction: Obesity and dyslipidemia are emerging as major public health challenges in South Asian countries. The prevalence of obesity is more in urban areas than rural. Increasing obesity and dyslipidemia in South Asians is primarily driven by nutrition, lifestyle and demographic transitions, increasingly faulty diets and physical inactivity, in the background of genetic predisposition. Aim: The aim of the study was to assess the glycaemic status with BMI and lipid profile in a group of official population of Bangladesh. Methodology: This prospective observational study was conducted in BIRDEM General Hospital during a period of one year from January 2013 to December 2013. 599 Working officials of 50 years of age and above were studied during their yearly health checkup. Body Mass Index (BMI) was used to assess the general obesity. This population group was also assessed for Metabolic Derangement by Fasting Blood Glucose, 2 Hours after Breakfast Blood Glucose, HbA1C and fasting Lipid Profile. Results: 470 out of 599 study populations had some form of glycaemic abnormality. Diabetes Mellitus Type-2 were found in 238 (39.73%), 113 (18.86%) had IGT and 119 (19.86%) had IFG. It was revealed from BMI assessment that 48.4% of the study population was overweight and 12.8% had obesity of different grades. All patients were evaluated for lipid status in fasting state. 326 (54.4%) had raised LDL, 361 (61.3%) low HDL and 289 (48.2%) had raised Triglycerides. Conclusion: This study reflects the high incidence of overweight subjects with more tendency to have lower HDL, high LDL and Triglyceride cholesterol. There was also high incidence of abnormal Glycaemic status in this specific small group of population focusing the future needs of thorough assessment at multicentre level in different groups of population to estimate the real scenario of the nation. Bangladesh Crit Care J March 2017; 5(1): 42-47